Overcoming Poverty: The Impact of Entrepreneurship Training - Andrade, Maureen Snow; Miller, Ronald Mellado; Seeley, Eugene (Journal of Applied Business and Economics, 2024)
Educational attainment may deter entrepreneurial activity. Educated individuals have greater job choice while lacking education can drive entrepreneurship out of necessity. Entrepreneurial training helps individuals learn the skills to launch businesses and become self-reliant. This study examined the efficacy of an entrepreneurial preparation program in Mexico by analyzing survey responses related to education and motivation. Findings indicate that factors other than training had more impact on business ownership. Motivational factors were positively correlated with the likelihood of being an entrepreneur. Mother’s education level was positively correlated with the likelihood of working for someone else.